2022
DOI: 10.1021/acs.est.2c02692
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Isotope Variations in Lake Sediment Cores in Response to Direct Mercury Emissions from Non-Ferrous Metal Smelters and Legacy Mercury Remobilization

Abstract: Nature archives record atmospheric mercury (Hg) depositions from directly emitted Hg and re-emitted legacy Hg. Tracing the legacy versus newly deposited Hg is still, however, challenging. Here, we measured Hg isotope compositions in three dated sediment cores at different distances from the Flin Flon smelter, the largest Canadian Hg sources to the atmosphere during the 1930s–2000s. During the smelter’s operative period, Hg isotope compositions showed limited variations in the near-field lake (<10 km) sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Local emissions from urban centers and smelters typically have less radiogenic 206 Pb /207 Pb ratios similar to leaded gasoline and coal combustion, 90 and the 1940 peak in radiogenic Pb is not found in other lakes in the northeastern United States. 27,28,85 The negative peak in δ 202 Hg is also difficult to tie to a local emission source; Hg isotopes from point sources such as smelter operations can have distinct δ 202 Hg and Δ 199 Hg from those typical of bulk anthropogenic emissions, 49 but there are no known historic smelter operations within the region. The peaks may therefore reflect a local re-release of deposited Pb and Hg.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Local emissions from urban centers and smelters typically have less radiogenic 206 Pb /207 Pb ratios similar to leaded gasoline and coal combustion, 90 and the 1940 peak in radiogenic Pb is not found in other lakes in the northeastern United States. 27,28,85 The negative peak in δ 202 Hg is also difficult to tie to a local emission source; Hg isotopes from point sources such as smelter operations can have distinct δ 202 Hg and Δ 199 Hg from those typical of bulk anthropogenic emissions, 49 but there are no known historic smelter operations within the region. The peaks may therefore reflect a local re-release of deposited Pb and Hg.…”
Section: Resultsmentioning
confidence: 99%
“…Terrestrial re-emission of Hg was recently shown to become the dominant source of deposition to lakes downwind of a point source, long after smelter emissions ceased. 49 Continued Pb deposition at remote sites, has also raised the possibility of watershed recycling of Pb, or of small, unaccounted emissions of Pb in modern times. 28 The continued presence of anthropogenic Hg and Pb, even at remote sites with no landscape disturbance, implies that long recovery times as well as stringent emissions standards are needed to control Hg contamination in remote lakes environments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations